Controlled synthesis of nanotubes and nanowires decorated with TiO2 nanocuboids with exposed highly reactive (111) facets to produce enhanced photoelectrochemical properties. Issue 94 (23rd September 2016) - Ding, Dong; Zhou, Bo; Feng, Shuang; Liu, Li; Feng, Fei; A, Runa; Su, Pengyu; Wang, Jun; Fu, Wuyou; Yang, Haibin
Abstract : We for the first time achieved a controllable synthesis of TiO2 nanocuboids with highly reactive (111) facets exposed and of a corresponding WT hybrid structure with enhanced photoelectrochemical properties. Abstract : The ability to control the exposure of facets of a crystal has been garnering considerable attention due to the fascinating dependence of the physical properties of crystals on their shapes. Herein, a TiO2 WT photoelectrode decorated with anatase TiO2 nanocuboids (TiO2 C111 WTs) displaying high-energy exposed (111) facets and quantum dot dimensions was prepared for the first time by using a TiCl4 treatment process. F − and NH4 + were introduced together to limit the randomness of the TiCl4 hydrolysates. We propose that both F − and NH4 + were necessary for controlling the exposure of the (111) facets. In comparison with TiO2 WT photoelectrodes decorated with either randomly deposited TiO2 nanoparticles (non-facet) or with TiO2 nanofilms or with TiO2 nanocuboids displaying exposed 001 facets (denoted as TiO2 PWT, TiO2 FWT and TiO2 C001 WT photoelectrodes, respectively), the hybrid-structured TiO2 C111 WT photoelectrode achieved superior PEC performances, with J sc and photoconversion efficiency values of 0.97 mA cm −2 and 0.49%. This enhancement was attributed to the exposure of the highly active (111) facets and the increased specific surface area of TiO2 C111 WTs. Meanwhile, the photoactive (111) facets offered oxygen vacancies, resulting in an increase of donor density and the enhancement of PEC performances. These facets also promoted the adsorption of CdS QDs and hence further sensitization. The CdS/TiO2 C111 WTs achieved J sc and photoconversion efficiency values of 3.95 mA cm −2 and 2.05%, which were about twice those of CdS/TiO2 WTs.